The Analysis Influence Economy Growth, Labor Education Level and Interest Rate on Investment in Maluku Province - Teddy Christianto Leasiwal; Bin Raudha A. Honoeboen (CV. Ridwan Publisher, 2023)
Investment in Maluku from year to year grows slowly, compared to its potential. To overcome the obstacles that hinder investment, the policies established by the regional government include accelerating the development and preparation of infrastructure supporting investment activities, creating a more conducive investment and business climate in the regions, developing human resources, both government and business actors in the regions. There are three variables, namely Economic Growth, Education and Interest Rates . The method of analysis used is multiple linear regression analysis. On result regression seen that the growth variable economy have connection positive , this is indicated by score coefficient as big as 5.363299 and has a significant influence significant to investment with a probability value of 0.0005. There is a positive relationship between the education level of the workforce and the level of investment with a coefficient value of 0.160310 . and very significant with a probability value of 0.0001. The interest rate has a negative effect on investment, with a coefficient value of -1.333418 meaning that an increase in the interest rate by 1% will also reduce investment by -1.333418 although the coefficient value is not significant.